A scoping review on developmental activities of girls' and women's sports - Peters, Carrie M.; Hendry, David T.; Hodges, Nicola J. (Frontiers in Sports and Active Living, 2022)
We provide a scoping review of research on athlete development in girls’ and women’s sports. Our emphasis is on pathways to expertise in the context of deliberate practice theory and associated models, such as the Developmental Model of Sport Participation (DMSP). Despite rationale for sex and gender differences in sport development, there are relatively few studies where the developmental pathways of female elite athletes have been evaluated. We sought to map the scope of the literature on this population over the last thirty years, focusing on measures of practice types and amounts. Following an extensive search of the literature, thirty-two studies were identified that included all female participants or presented sex/gender disaggregated data. Retrospective methods were commonly used to quantify practice, play and specialization. National-level athletes were the most represented, although there was considerable heterogeneity in sport and expertise-level, making general or comparative judgements challenging. We identified some groups who had accumulated high volumes of practice at a young age, particularly in soccer and rhythmic gymnastics. However, these athletes deviated from predictions in the specialization pathway detailed in the DMSP, by continuing to participate in other sports throughout childhood and adolescence. Most athletes followed a diversified sport pathway before majority engagement in their primary sport in adolescence. Athletes who had more diversified sport profiles in early childhood continued to participate in other sports throughout adolescence. In addition to highlighting the relative paucity of data pertaining to athlete development pathways in female athletes, we show that the data from these groups deviate from predictions detailed in current models of athlete development.